Host–microbial co-metabolites modulated by human milk oligosaccharides relate to reduced risk of respiratory tract infections - Martin, François-Pierre; Tytgat, Hanne L. P.; Krogh Pedersen, Helle; Moine, Deborah; Eklund, Aron C.; Berger, Bernard; Sprenger, Norbert (Frontiers in Nutrition, 2022)
Human Milk Oligosaccharides (HMOs) are structurally diverse oligosaccharides present in breastmilk, supporting the development of the gut microbiota and immune system. Previously, 2-HMO (2'fucosyllactose, lacto-N-neotetraose) compared to control formula feeding was associated with reduced risk of lower respiratory tract infections (LRTIs), in part linked to lower acetate and higher bifidobacteria proportions. Here, our objective was to gain further insight on additional molecular pathways linking the 2-HMO formula feeding and LRTI mitigation. From the same trial, we measured the microbiota composition and 743 known biochemical species in infant stool at 3 months of age using shotgun metagenomic sequencing and untargeted mass spectrometry. We used multivariate analysis to identify biochemicals associated to 2-HMO formula feeding and LRTI and integrated those finding with the microbiota compositional data. Three molecular pathways stood out: increased gamma-glutamylation and N-acetylation of amino acids and decreased inflammatory signaling lipids. Integration of stool metagenomic data revealed some Bifidobacterium and Bacteroides species to be implicated. These findings deepen our understanding of the infant gut/microbiome co-metabolism in early life and provide evidence for how such metabolic changes may influence immune competence at distant mucosal sites such as the airways.